A dynamic systems account of parental self‐regulation processes in the context of challenging child behavior. Issue 5 (30th May 2022) - Zhang, Xutong; Gatzke‐Kopp, Lisa M.; Cole, Pamela M.; Ram, Nilam
Abstract: To advance the understanding of how parental self‐regulation contributes to their role in supporting children's development, this study proposes a model of the dynamic processes involved in parental self‐regulation. Based on time‐series data from 157 mothers and their 30‐ to 60‐month‐old children (49.7% female; 96% White; data collected June 2017–December 2019 in central Pennsylvania, U.S.) during a challenging wait task, the model was tested by examining the temporal relations among challenging child behavior, maternal physiology, and maternal responsiveness. Results were consistent with the hypothesized dynamic negative feedback processes and revealed their associations with the overall quality of parenting behaviors and experiences. Findings elucidate how parents adapt to competing external (attending to child) and internal (restoring parents' equilibrium) demands during parenting challenges.